The prognostic nomogram including MRI for locally advanced prostate cancer treated by radical prostatectomy. Issue 8 (6th April 2021) - Wang, Yan; Wu, Guangyu; Fan, Liancheng; Pan, Jiahua; Gong, Yiming; Fei, Xiaochen; Du, Xinxing; Zhu, Yinjie; Xue, Wei
Abstract: Objective: To establish the prognostic nomogram for locally advanced prostate cancer (LAPC) patients treated by radical prostatectomy (RP) based on clinical and multiparametric‐MRI (mp‐MRI) metrics. Methods: One hundred and twenty‐one patients diagnosed with LAPC were included in this study. They were all examined by mp‐MRI within one week before surgery and treated by RP (36 with RP alone, 48 with neoadjuvant hormonal therapy (NHT) and 37 with neoadjuvant chemohormonal therapy (NCHT)). The biochemical progression‐free survival (bPFS) was analyzed by Kaplan–Meier method. Univariate and multivariate analysis were used to determine prognostic factors that were related with bPFS. The prognostic nomogram was established by factors that were significant in multivariate analyses. Results: The median bPFS had significant difference in the subgroup of treatment (RP alone: 2 [0.00–5.04] vs. NHT: 9.3 [6.746–11.854] vs. NCHT: 11.17 [0.000–25.075] months [Log rank p  < .001]), the subgroup of hyperintensity within prostate in DWI (negative: 15.97 [11.202–20.731] vs. positive: 5.2 [2.952–7.448] months [Log rank p  < .001]) and the subgroup of pelvic lymph node metastasis (negative: 10.2 [8.404–11.996] vs. unilateral: 4.43 [0.000–11.086] vs. Bilateral: 1.83 [0.636~3.031] [Log rank p  < .001]). The method of treatment (hazards ratio [HR], 0.566; 95% confidence interval [CI], 0.356–0.899; p  = .016), hyperintensity within prostate in DWI (HR, 2.539; 95% CI, 1.349–4.779; p  = .004) and the metastasis burden of pelvic lymph node (HR, 2.492; 95% CI, 1.645–3.777; p  < .001) were identified as independent predictors with significance in multivariable Cox regression analysis. The nomogram was established based on these three factors. Conclusion: We established a nomogram based on three significant prognosis factors including the neoadjuvant therapeutic schedule, hyperintensity within prostate in DWI and the metastasis burden of pelvic lymph nodes, which were associated with the clinical outcomes in LAPC patients after surgery.